Rhenium-osmium and oxygen isotope homogeneity during the 2022 Mauna Loa eruption and implications for basaltic magma storage - Emily A. Rhoads; Anton Kutyrev; Ilya N. Bindeman; Kendra J. Lynn; Frank A. Trusdell; Drew T. Downs; Hunter R. Edwards; Geoffrey W. Cook; James M. D. Day (Bulletin of Volcanology, 2025)
Mauna Loa is one of the largest and most active volcanoes on Earth. The most recent eruption of Mauna Loa started on 27 November 2022, lasted for 13 days, and was preceded by the longest repose time of 38 years in its modern history. In this contribution, new trace- and highly siderophile-element (HSE: Os, Ir, Ru, Pt, Pd, Re) abundances, 187 Re- 187 Os, and 18 O/ 16 O data are reported for the 2022 lavas. These lavas have a limited range of MgO (6.2 ± 0.1 wt.%) and Ni (83 ± 2 µg/g), with a broader range of Re (0.3 to 1.3 ng/g) and consistent Os (0.031 to 0.080 ng/g) contents. They have 187 Os/ 188 Os ratios (0.1345 to 0.1385) which are, on average, more radiogenic than Mauna Loa picrites (0.1331 to 0.1349) and are similar in composition to more differentiated Mauna Loa tholeiite lavas (0.1340 to 0.1381). The oxygen isotope compositions of glassy samples are 5.35 ± 0.15‰ ( n = 13) and span a range in δ 18 O of + 5.0 to + 5.5‰, with an average composition 0.2 to 0.3‰ lower than MORB. The δD value is − 81 ± 11‰ ( n = 5) at very low (0.03 ± 0.015 wt.%) H 2 O concentrations. The 2022 Mauna Loa eruption is similar in terms of δ 18 O but contrasts in terms of 187 Os/ 188 Os variability, with the recent longer-lived eruptions on La Palma (Canary Islands; 85 days) in 2021 and on the Reykjanes Peninsula (Iceland) that began in 2021 and are still ongoing. Initial lavas were more fractionated for both the Canary Islands and Iceland eruptions, producing more radiogenic Os isotope compositions than later erupted products. The 2022 Mauna Loa eruption showed no such trends. The limited range in isotope compositions of the 2022 Mauna Loa lavas and their strongly fractioned HSE patterns reflect long-term storage, crystal fractionation, and assimilation of related basaltic volcanic edifice materials by the parent magma beneath the volcano prior to eruption triggering. Eruption of differentiated and homogeneous tholeiite lavas at the summit caldera and high on the volcano’s flank, with emplacement of accumulative picrites lower on the volcano, are consistent with neutral buoyancy arguments.